IMPLEMENTASI MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Putri, Rahmah Dianti (Jurnal Pendidikan Progresif, 2016)
Implementation of Inquiry Learning to Enhance Students’ Critical Thinking Skill. This research was aimed at investigating the use of inquiry learning model to improve students’ critical thinking in the course of Non Banks and Banking Financial Institutions and the effectiveness of using inquiry learning model in that course. There are 53 third semester students of Economics Education Study Program from FKIP UNILA 2016/2017 who takes non Bank and Banking financial institutions course as the subject of this reserach while the object of this reserach was inquiry-based learning model. This research was Classroom Action Research which used a developed model from Kemmis and Mc Taggart with four components in every cycle; planning, action, observation, and reflection. The observation result from the first cycle described that there are 68.50% students who has done critical thinking activity while in the second cycle, there are 97.69% students. This research was conducted in two cycles and since in the second cycle the result has shown the improvement. From this result, it showed that there is an improvement in students’ critical thinking ability who takes non Bank and Banking financial institutions course. Based on this result, it can be suggested that inquiry learning model is effective to be implemented in the course of non Bank and Banking financial Keywords: inquiri model learning, non bank institutional, banking institutins DOI: http://dx.doi.org/10.23960/jpp.v6.i2.201601